2019
DOI: 10.1108/jfra-06-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Firm characteristics and compliance with IAS/IFRS

Abstract: Purpose This paper aims to examine the influence of firm characteristics on harmonisation of companies listed on the Egypt, Morocco and Tunisia Stock Exchanges. Design/methodology/approach This study uses a checklist based mainly on the International Financial Reporting Standards (IFRS). Findings The findings of the study are 6that the level of compliance with IFRS was higher in 2010 than in 2005. Multiple regression analysis indicates that the level of compliance with IFRS increases with company size, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 138 publications
(225 reference statements)
1
8
0
2
Order By: Relevance
“…The findings are thus in line with the conclusions of Tsalavoutas (2011), which found, in a more crosssectional study on the subject, differences between the levels of disclosures for IAS 19, IAS 36, and IAS 37. It also corroborates, in another perspective, the divergences between the levels of disclosure identified and the different studies that used, individually, the same IAS and IFRS proposed in this study, namely for IFRS 13 (Kasyan et al, 2018;Matiş et al, 2013), IAS 19 (Street & Gray, 2002), IAS 36 (Glaum et al, 2013;Paugam et al, 2013), and IAS 37 (Alnaas & Rashid, 2019).…”
Section: Discussion Of Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The findings are thus in line with the conclusions of Tsalavoutas (2011), which found, in a more crosssectional study on the subject, differences between the levels of disclosures for IAS 19, IAS 36, and IAS 37. It also corroborates, in another perspective, the divergences between the levels of disclosure identified and the different studies that used, individually, the same IAS and IFRS proposed in this study, namely for IFRS 13 (Kasyan et al, 2018;Matiş et al, 2013), IAS 19 (Street & Gray, 2002), IAS 36 (Glaum et al, 2013;Paugam et al, 2013), and IAS 37 (Alnaas & Rashid, 2019).…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…Regarding size, the literature is identified in line with the initial propositions, with a predominance of investigations that find a positive association (Ali et al 2004;Alkababji, 2016;Alnaas & Rashid, 2019;Demir & Bahadir, 2014;Devalle & Rizzato, 2013;Guerreiro, 2006;Lopes & Rodrigues, 2007;Matiş et al, 2013;Oliveira & Lemes, 2011;Owusu-Ansah, 1998;Richardson & Welker, 2001;Santos et al, 2014;Singhvi & Desai, 1971;Street & Gray, 2002;Wallace & Naser,1995;Zarzeski, 1996). On profitability, there is research that found a positive relationship (Ali et al, 2004), but also the opposite (Wallace & Naser, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 76%
“…Similarly, Elghaffar et al (2019) found an increase in the level of risk disclosure in Egyptian banks, and Ebrahim and Abdel Ebrahim and Fattah (2015) an increase in the level of compliance with the requirements of IAS 12 in Egyptian companies. Moreover, Alnaas and Rashid (2019) demonstrate that compliance with IFRS in companies in North African countries (Morocco, Tunisia, Egypt) is positively affected by institutional ownership.…”
Section: Institutional Ownershipmentioning
confidence: 94%
“…Bananuka et al (2019a) and Bananuka et al (2019b) found that ownership structure and capital structure are not significant predictors of IFRS adoption. However, Alnaas and Rashid (2019) suggest that ownership structure increases the level of compliance with IFRS. The operationalization of the main study variables as well as control variables are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%